If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6x + -2) = 2(3x + 5) Reorder the terms: 4(-2 + 6x) = 2(3x + 5) (-2 * 4 + 6x * 4) = 2(3x + 5) (-8 + 24x) = 2(3x + 5) Reorder the terms: -8 + 24x = 2(5 + 3x) -8 + 24x = (5 * 2 + 3x * 2) -8 + 24x = (10 + 6x) Solving -8 + 24x = 10 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -8 + 24x + -6x = 10 + 6x + -6x Combine like terms: 24x + -6x = 18x -8 + 18x = 10 + 6x + -6x Combine like terms: 6x + -6x = 0 -8 + 18x = 10 + 0 -8 + 18x = 10 Add '8' to each side of the equation. -8 + 8 + 18x = 10 + 8 Combine like terms: -8 + 8 = 0 0 + 18x = 10 + 8 18x = 10 + 8 Combine like terms: 10 + 8 = 18 18x = 18 Divide each side by '18'. x = 1 Simplifying x = 1
| 2x+1y=29 | | -4d(2d+3)=3(-4d-4) | | 23=8x | | 5v^2-10v-40=0 | | (2x+1)-2(x-5)+6=3x(x+1)+(x-1)+23 | | 4(7v-2)-7=4(1+7v) | | 4k(3+k)=-(2k+3) | | -9(z+5)=0 | | -9(z+6)=0 | | x(x-3)-x(x+5)+6=-2 | | 1-7n-2n=-8 | | 7-a=15a-2a | | -16x^2+3x+1.3=0 | | (23+5x)=(14x-3) | | 3(n-8)=4(n+2) | | (2n+5)(2n+3)=0 | | R=5x+43 | | (4g+7)+(7g+2)= | | 23+5x=14x-3 | | 4(c-3)+5=2c+3 | | 6(m+1)=3m-3 | | -3(a+4)=6 | | -g+6+2g=4g+4 | | 6x+7=2x-13 | | 12-1.7x=4.15 | | (x+1)+2(x-3)-5=(x+2)-(x+3)+2 | | ln(5x+3)=4 | | 27-3(2x+3)=2(1-3x) | | 7-n-6=-13+6n | | 12x^2+9x-20=0 | | 5(2.6x+3.9)=5 | | cos(2x)-5cosx+3=o |